Morphological and morphometric changes in the faces of female-to-male (FtM) transsexual people. Issue 2 (3rd April 2017) - Mackenzie, Stenton; Wilkinson, Caroline
ABSTRACT: Facial changes associated with the administration of exogenous testosterone and bilateral oophorectomy in female-to-male (FtM) transsexual people (trans men; trans males) has not been previously documented. This study aimed to describe the qualitative and quantitative transformation from a female to a male facial appearance and to identify predictable patterns of change. Twenty-five trans men were studied using morphological and morphometrical analysis of pre-transition 2-D images and post-transition 3-D scan models. The mean subject age was 39 years and all subjects had been taking testosterone for at least 3 years, with a mean duration of therapy of 8.6 years. While 32% of subjects were classified by a majority of observers as male appearing in pre-transition photographs, this rose to 95.5% in post-transition images. Eighty-six percent of subjects demonstrated an increase in male classification after transition. Morphometrically, 44% of subjects became wider in the face overall and 100% of subjects measured demonstrated a narrower nose after transition. Testosterone virilizes adult female faces and will cause widening of the face. The most consistent facial change was the production of a narrower nasal width at the alae, which may be a result of fat re-deposition not related to ageing effects or body mass index (BMI).